Evaluation of the First Commercial Hepcidin ELISA for the Differential Diagnosis of Anemia of Chronic Disease and Iron Deficiency Anemia in Hospitalized Geriatric Patients. (29th February 2012) - Geerts, Inge; Vermeersch, Pieter; Joosten, Etienne
Abstract : Introduction . Anemia is a frequent problem in hospitalized geriatric patients, and the anemia of chronic disease (ACD) and iron deficiency anemia (IDA) are the 2 most prevalent causes. The aim of the study was to assess the possible role of serum hepcidin in the differential diagnosis between ACD and IDA. Methods . We investigated serum hepcidin, iron status, anemia, and C-reactive protein in 39 consecutive geriatric patients with ACD and IDA. Serum hepcidin levels were determined using a commercial ELISA kit (DRG Instruments, Marburg, Germany). We also measured hepcidin in 26 healthy controls. Results . The serum hepcidin levels were not significantly higher in the 28 patients with ACD as compared to the 11 patients with IDA. Conclusions . The serum hepcidin levels measured using the commercial ELISA kit (DRG) do not appear to increase in older patients with ACD. It should be noted that an assay-specific problem could explain our results.